Screening Race in American Nontheatrical Film - Gordon, Marsha; Field, Allyson Nadia (Duke University Press, 2019)
Although overlooked by most narratives of American cinema history, films made for purposes outside of theatrical entertainment dominated twentieth-century motion picture production. This volume adds to the growing study of nontheatrical films by focusing on the way filmmakers developed and audiences encountered ideas about race, identity, politics, and community outside the borders of theatrical cinema. The contributors to Screening Race in American Nontheatrical Film examine the place and role of race in educational films, home movies, industry and government films, anthropological films, and church films, as well as other forms of nontheatrical filmmaking.